The institutional logics of local government budget in Indonesia - Palupi, Ade; Febiandra, Refinaldo (2017)
This study asks how and why a local government settings budget.It aims to deliver an understanding on how a government entity perceives that budget is important element to manage public expenditures.It uses the S local government in Indonesia as a case study.This study applies Institutional Logics Theory as a theoretical framework in order to analyze data. Data is collected by interviewing seven key persons who directly involves in budgeting process.This research shows that the budgeting process includes determining the purposes of annual budget, setting up planned programs and actvities, determining the amount of revenue that will be collected, allocating resources to expenditures and setting up standar pricing.Some important points in the budgeting process are identified.Those are considering political aspect to determine local tax rate, focusing on competition with other local governments, fulfilling the political promise of local government leader to the constituents, involving community to determine planned program and activities, and allocating resources based on community basic needs.This study concludes that those points develop the institutional logics of politic and managerial in budget setting process.